2018
DOI: 10.1002/ejoc.201801601
|View full text |Cite
|
Sign up to set email alerts
|

A Micellar Catalysis Strategy for Amidation of Alkynyl Bromides: Synthesis of Ynamides in Water

Abstract: Copper‐catalyzed amidation of alkynyl bromides can be carried out in water for the first time, which is made possible by a micellar catalysis strategy using rosin‐based surfactant APGS‐550‐M. The surfactant can be easily prepared from natural abundant biomass, resin acids. Studies as to substrate scope and reaction aqueous medium recycling showcase the ease and sustainability of this technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 69 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…The surfactant, prepared by Yang et al, was shown to be highly effective in facilitating Cu-mediated amidation of alkynyl bromides under aqueous-micellar conditions, see Scheme 7 . 257 Normally, this type of transformation is conducted in dry solvents such as DMF, DMSO, or toluene at elevated temperatures. Side-reactions that can occur include homocoupling of alkynes to give 1,3-diynes, hydration of the diynes to furans, and hydration of ynamides to amides; 257 thus, the presence of water in the system is somewhat counterintuitive.…”
Section: Selection Of Alternative Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surfactant, prepared by Yang et al, was shown to be highly effective in facilitating Cu-mediated amidation of alkynyl bromides under aqueous-micellar conditions, see Scheme 7 . 257 Normally, this type of transformation is conducted in dry solvents such as DMF, DMSO, or toluene at elevated temperatures. Side-reactions that can occur include homocoupling of alkynes to give 1,3-diynes, hydration of the diynes to furans, and hydration of ynamides to amides; 257 thus, the presence of water in the system is somewhat counterintuitive.…”
Section: Selection Of Alternative Solventsmentioning
confidence: 99%
“… 257 Normally, this type of transformation is conducted in dry solvents such as DMF, DMSO, or toluene at elevated temperatures. Side-reactions that can occur include homocoupling of alkynes to give 1,3-diynes, hydration of the diynes to furans, and hydration of ynamides to amides; 257 thus, the presence of water in the system is somewhat counterintuitive. However, the micellar conditions allow for smooth conversion of bromoalkynes to the corresponding ynamides.…”
Section: Selection Of Alternative Solventsmentioning
confidence: 99%
“…For the preparation of sulfonamide compounds of type 1 and 2 (Figure 3), several procedures are present in the literature [54][55][56][57][58][59][60][61], and a few of them were also proposed recently in light of using more environmentally friendly green chemistry approaches [62][63][64][65][66].…”
Section: Synthesismentioning
confidence: 99%
“…A variety of such nonionic benign by design surfactants is all considered PEGylated amphiphilic species, with or without a linker. TPGS-750-M [24], PQS [25], SPGS-550-M [26], Coolade [27], DAPGS-750-M [28], APGS-550-M [29], MC-1 [30], PTS [31], SMPS [32], BTBT-750-M, PiNAP-750-M [33], TPGlite [34], or PS-750-M [35] are some of the most studied excipients (Scheme 1). They have been demonstrated to be extremely versatile, most notably TPGS-750-M and PS-750-M, and shown to function as suitable surrogates to reprotoxic polar aprotic solvents, thus offering a real opportunity to phase out such solvents.…”
Section: Water Chemistry Enabled By Surfactantsmentioning
confidence: 99%